Political Elite under Manuel II Palaiologos: the Evolution of the Court Hierarchy - Tatyana V. Kushch (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
This paper will focus on the political elite of Byzantium in the late fourteenth and early fifteenth centuries and the changes in its structure. According to the analysis of prosopographic data, the number of the ruling elite considerably decreased during the reign of Manuel II Palaiologos. The hierarchy of titles and offices declined, so that many of them, even of supreme level, were not granted anymore, and later disappeared from political life. The central administrative machinery was reduced to the size of the imperial court. The ruling elite incorporated the descendants of famous Byzantine families and persons who established friendly relations with Manuel II. The emperor considerably raised the role of his intellectual retinue. Often without official titles and positions, the intellectuals, nevertheless, became key figures in the empire’s political affairs.